Nitrene Transfer Catalyzed by a Non-Heme Iron Enzyme and Enhanced by Non-Native Small-Molecule Ligands - Goldberg, Nathaniel W; Knight, Anders M; Zhang, Ruijie K; Arnold, Frances H (Journal of the American Chemical Society, 2019)
Transition-metal catalysis is a powerful tool for the construction of chemical bonds. Here we show that Pseudomonas savastanoi ethylene-forming enzyme, a non-heme iron enzyme, can catalyze olefin aziridination and nitrene C–H insertion, and that these activities can be improved by directed evolution. The non-heme iron center allows for facile modification of the primary coordination sphere by addition of metal-coordinating molecules, enabling control over enzyme activity and selectivity using small molecules.